Factors affecting the Perception of Farmers about Climate Change in Agriculture - Nanjappan, Balasubramani; Parameswaranaik, J (Journal of Agricultural Extension Management, 2019)
Climate is a critical factor in the livelihoods of people and socioeconomicdevelopment as a whole, however the recent developments have adversely affected climate and its effect is seen in all the sectors. Among these different sectors, agriculture is highly sensitive to climate change where a large number of small and marginal farmers depend on agriculture and allied activities for their livelihood. In view of this, a study was undertaken in two states having different vulnerabilities to climate change with an objective of assessing the perception of farmers about climate change in agriculture and factors associated with their perception. The study reveals that a majority of the respondents perceived that the summer temperature is increasing during daytime (84.44% and night time (68.89%), water requirement for the crops has increased (80.00%). The variables such asage, education, extension contact and mass media had a positive and significant relationship at one percent level of probability. Hence, timely access to extension services and weather information are crucial in shaping the perception of farmers about climate change.